(untitled) (Research, Society and Development, 2020)
This text aims to present reflections on bullying with hemophiliacs in schools, as well as problematize possible dialogues based on the principles of Social Education and Social Education in Health. For this, the Brazilian academic production on the themes Bullying, Hemophilia, School, Education Social and Social Education in Health was used. The search was carried out in two web databases: the Brazilian Digital Library of Theses and Dissertations (BDTD), and the Scientific Electronic Library Online (SCIELO). The results showed that the principles of Social Education and Social Education in Health provide a condition of visibility to the public that for a long time was outside the social framework.